A novel mRNA-based multiepitope vaccine candidate against Cryptosporidium hominis and Cryptosporidium parvum employing reverse-vaccinology and immunoinformatics approaches - Ahmad Abdullah Mahdeen; Imam Hossain; Md. Habib Ullah Masum; T. M. Fazla Rabbi; Sajedul Islam (PLoS ONE, 2026)
Introduction The parasite Cryptosporidium spp. causes cryptosporidiosis, a diarrheal disease in humans and animals. This study describes the development of mRNA vaccine targeting antigens from C. hominis and C. parvum , important gut pathogens. This vaccine was designed with reverse vaccinology and immunoinformatics as no FDA-approved vaccine exists for cryptosporidiosis. Materials and methods Initially, a thorough literature review was conducted to identify five pathogenic proteins (aminopeptidase, heat shock protein, P23, serine protease, and sporozoite glycoproteins) associated with these two parasites. Next, a multiple sequence alignment was conducted, and the conserved sequences were used to design a novel multiepitope mRNA vaccine against these two parasites, combining the best CD8+, CD4+, and continuous B-cell epitopes. Additionally, structural prediction, docking, dynamics, and immune simulation, as well as cloning, were conducted. Result The vaccine demonstrated standard biophysical properties, indicating that the protein is soluble and stable. Both two-dimensional (substantial alpha helix, beta sheet, and coil structures) and three-dimensional structures (Ramachandran score of 83.1% and a Z score of −7.39) of the vaccine were standard. The docking energy for TLR-2 (−1151.9) and TLR-4 (−1028.3) exhibited significant interactions. Furthermore, MM-GBSA and dynamics simulation both verified their stability, compactness, and flexibility. Next, codon optimization for Escherichia coli expression yielded promising results, with the vaccine demonstrating substantial expression, as evidenced by a GC content of 46.97% and a CAI of 0.988. Afterwards, immune simulation demonstrated robust immune response amplification upon repeated exposures. In addition, the vaccine exhibited stability in its mRNA structures. Conclusion This study developed an i n-silico multiepitope novel mRNA vaccine candidate for C. hominis and C. parvum with excellent structural stability, antigenicity, receptor-binding affinity, and expected immune responses. These findings offer a novel approach due to numerous species target but with significant drawbacks like no validation beyond simulation, uncertainty of long-term immunity, protein quality, stability and safety, requiring experimental validation.